M. Shuler diary - Shuler, M.
Two volume diary (1862 June 11-December 12) kept by Shuler while serving with the 33rd Virginia Infantry Regiment, Confederate States Army, during the Peninsular, Second Bull Run, Antietam, and Fredericksburg campaigns. Includes information on casualties, marches, discipline, supplies, depradations, and morale. Also mentions battles of Malvern Hill and Cedar Mountain, capture of Harpers Ferry, and the burning of public buildings in Martinsburg, W. Va.
Confederate army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Confederate States of America. -- Army. -- Virginia Infantry Regiment, 33rd.; Antietam, Battle of, Md., 1862.; Bull Run, 2nd Battle of, Va., 1862.; Cedar Mountain, Battle of, Va., 1862.; Fredericksburg, Battle of, Fredericksburg, Va., 1862.; Malvern Hill, Battle of, Va., 1862.; Peninsular Campaign, 1862.; Harpers Ferry (W. Va.) -- History -- Siege, 1862.; Martinsburg (W. Va.) -- History -- Civil War, 1861-1865.; Maryland -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Casualties; United States -- History -- Civil War, 1861-1865 -- Equipment and supplies, Confederate; United States -- History -- Civil War, 1861-1865 -- Personal narratives, Confederate; United States -- History -- Civil War, 1861-1865 -- Psychological aspects; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; West Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Army officers, Confederate